Effect of sugarcane molasses extract on the formation of 2-amino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (PhIP) in a model system. (15th April 2016) - Yu, Di; Chen, Ming-Shun; Yu, Shu-Juan
Highlights: Sugarcane molasses extract inhibited the formation of PhIP is first proposed. A pathway of phenolic compounds inhibited the formation of PhIP is proposed. Sugarcane molasses extract may be applicable to food system as a food additive. Abstract: Molasses, the main by-product of sugar production, is a well-known source of antioxidants. In this study, sugarcane molasses extract was investigated for its total phenolic content and in vitro antioxidant capacity. The experimental total phenolic content was 101.3 mg of gallic acid equivalent (GAE) in 1 g of extract, IC50 of Trolox and sugarcane molasses extract were 125.33 μg/ml and 126.0 μg/ml, respectively. A chemical model system showed that the sugarcane molasses extract effectively reduced the formation of phenylacetaldehyde and the aldol condensation product, meanwhile, the amount of 2-amino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (PhIP) also decreased. This could be due to the reaction between the phenolic compounds of sugarcane molasses extract and the carbonyl group of phenylacetaldehyde inhibiting the aldol condensation product formation, and this would suppress the formation of PhIP. A pathway that phenolic compounds inhibited the formation of PhIP is proposed. This pathway also suggested a mechanism for how the sugarcane affects the formation of PHIP.